2020
DOI: 10.1108/jfc-03-2020-0032
|View full text |Cite
|
Sign up to set email alerts
|

Financial C.R.I.M.Es in small businesses: causes and consequences

Abstract: Purpose The purpose of this paper is to examine the causes and consequences of financial crimes perpetrated against New Zealand small businesses. Design/methodology/approach A random sample of 200 court cases was selected from 2010 to 2017. A total of 12 cases involving 14 small businesses were analysed. Findings The results reveal that financial crime is a systemic problem and involves people with diverse demographics, and the victims are not restricted to any specific type of small business. The offender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…However, fraud also occurs due to gender nepotism (Wellalage et al , 2019) in which women owners are discriminated against regarding lending lend money from a financial institution. This is like Othman et al (2020) studies in which women committed fraud as they are responsible for the organisation’s finances and have opportunities to manipulate the finances of the SME. Besides that, fraud happened among employees because of low morale among them (Gunasegaran et al , 2018; Omar et al , 2016), difficult family situations (Gunasegaran et al , 2018; Andoh et al , 2018), lower payment (Omar et al , 2016; Andoh et al , 2018), unfair treatment (Andoh et al , 2018), low bond and loyalty to the company as they are new to the company (Omar et al , 2016) and peer pressure (Omar et al , 2016).…”
Section: Discussion Of Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, fraud also occurs due to gender nepotism (Wellalage et al , 2019) in which women owners are discriminated against regarding lending lend money from a financial institution. This is like Othman et al (2020) studies in which women committed fraud as they are responsible for the organisation’s finances and have opportunities to manipulate the finances of the SME. Besides that, fraud happened among employees because of low morale among them (Gunasegaran et al , 2018; Omar et al , 2016), difficult family situations (Gunasegaran et al , 2018; Andoh et al , 2018), lower payment (Omar et al , 2016; Andoh et al , 2018), unfair treatment (Andoh et al , 2018), low bond and loyalty to the company as they are new to the company (Omar et al , 2016) and peer pressure (Omar et al , 2016).…”
Section: Discussion Of Resultsmentioning
confidence: 98%
“…However, Othman et al (2020) used the C.R.I.M.E model introduced by Rezaee (2005) to explore financial fraud in small businesses in New Zealand. Therefore, the C.R.I.M.E model which consists of cooks, recipes, incentive, monitory and end-result were used to be chronological strategies towards their studies.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The SFO acknowledges that New Zealand faces complex and rapidly changing financial crimes and corruption threats (SFO, 2021, p. 11) and the national fraud policy agenda had to compete with other national priorities (Doig & Levi, 2013). The full scale of fraud in New Zealand remains unknown, although previous research has claimed that most frauds are perpetrated in the workplace (KPMG, 2020; Othman et al, 2020b). For example, in Case 2014-224.…”
Section: Study Contextmentioning
confidence: 99%
“…These cases are classified as a new category: 'gang and peer influence'. Othman et al (2020) suggested that, if the motives are not financial, they might be psychologically motivated, feeling good in doing it or to 'keep going'. These motivations account for 9.2 per cent of the total.…”
Section: Gender Of Fraudstersmentioning
confidence: 99%
“…Psychological reasons could be used as the line of defence in court (Othman et al., 2020). Our data show that six of our fraudsters claimed that their mental issues were the main reason for their offences.…”
Section: The Pressuresmentioning
confidence: 99%